Football goes east : business, culture and the people's game in China, Japan and South Korea - Manzenreiter, Wolfram; Horne, John, 1955- (Routledge, 2004)
Global popular culture and big business have revolutionised the East in a generation. Football, Sport of the masses and now commercial super power, has travelled with this tide of change in the East in its own right.